Opposites attract: The case of Greek and Turkish financial markets - Konstantinos Drakos; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
We investigate the presence of financial linkages between Turkey and Greece. In particular, we estimate bivariate vector error correction systems between the Greek and Turkish stock markets and then between the Greek Drachma and the Turkish Lira to test for long and short run causality and interdependence. The findings indicate that interdependence and a long-run causal relationship are indeed present. Given the apparent evidence for nominal linkages, we test a number of possible propagation mechanisms that could produce these linkages, such as real linkages, trade linkages, common balance of payments shocks, and contagion. Our findings suggest that the observed comovement of the two markets can be primarily attributed to the increased real integration of both countries, as well as the fact that they share a common set of trade and FDI partners. We also find evidence of contagion effects between the Drachma and Lira markets, but not between the stock markets. Finally, we conclude with a discussion of the implications of our findings.
Keywords: 330; Cointegration; Contagion; Interdependence; Market Linkages; Finanzmarkt; Internationaler Preiszusammenhang; Aktienmarkt; Wechselkurs; Marktintegration; Kointegratio